A 3D printed hand model of Bennett’s and 5th metacarpal shaft fractures (Transactions on Additive Manufacturing Meets Medicine, 2025)
Percutaneous fracture fixation of hand fractures using Kirschner wires is a difficult skill for learners to develop due to difficulties in spatial visualization, fracture alignment, fluoroscopic guidance, and instrument handling. Realistic models are required to improve surgical education and skill acquisition outside the operative setting. This study examines the utilization of 3D printing, silicone casting, and electromagnetic (EM) tracking to fabricate reproducible multi-material hand fracture models simulating Bennett’s and 5th metacarpal shaft fractures. CT images of a healthy hand were segmented to create 3D reference meshes for bones and skin. Artificial fractures were introduced and the skin mesh updated to reflect displacements. Bone meshes were modified for 3D printing and EM integration by incorporating features such as fracture bridging, through-holes for silicone adhesion, wire channels for sensor placement, registration fiducials, and a baseplate for mold alignment.
Keywords: 3D printing; casting; bone fracture; surgery practice